Challenges and Barriers of Technology Adoption Among Women in Open and Distance Learning: Evidence from Botswana - Majoo, Pulafela Akofhang; Rafifing, Neo; Mabina, Alton; Tlhoolebe, Joyce; Gadilatolwe, Innocent (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
This study explores gender-specific challenges that affect women’s adoption of technology in Open and Distance Learning (ODL) in developing countries, focusing on Botswana. It addresses the limited empirical understanding of how socio-economic, cultural, and digital literacy factors shape women’s ability to engage with technology-mediated education. A cross-sectional survey was conducted with 20 women enrolled in ODL programs, collecting data on technology access, digital competence, socio-economic background, and perceptions of institutional support. Descriptive and inferential statistical analyses, including correlations and chi-square tests, were conducted using SPSS. The findings show that limited digital literacy and poor internet access are the main barriers, while higher education and income levels positively impact technology engagement. Socio-cultural norms and institutional support also play a role, though shifting gender roles are reducing traditional constraints. This study highlights the intersection of individual competencies and contextual factors, providing evidence of both technological and socio-cultural determinants of women’s participation in ODL. The results inform policy and suggest areas for future research on inclusive digital education strategies.